Espectrofotometria no infravermelho por metodologia FTIR (Fourier Transform Infrared): validação da análise do teor de uréiae de outros parâmetros de qualidade do leite - Maria Carolina Pais Pinto de Oliveira (2011)
The objective of this study was to perform the validation of equipment based on Fourier Transform Infrared methodology (FTIR) to evaluate the content of milk urea nitrogen (MUN) in Brazil. Repeatability and reproducibility of CombiScope FTIR, urea stability and comparison with an enzymatic automated method (Chemspec®150; Bentley Instruments) were tested. The equipment CombiScope FTIR showed good precision and accuracy in repeatability and reproducibility for the measurement of raw milk urea nitrogen (MUN), as well as for the other components. There was no significant difference (p > 0.05) between the results for MUN by FTIR and enzymatic method. FTIR detection of extraneous urea intentionally added to raw milk showed a significant difference at addition level of 40 mg/dl, and a lower accuracy, compared to the urea analyzer by enzymatic methods. The levels of urea in raw milk after three days of storage at 20°C were higher. Raw milk components (fat, protein, lactose and solids nonfat) were stable at temperatures of 4°C and 20°C during 15 days of storage. Moreover, there was an increase in SCC during storage of the samples at 20°C. pH values in raw milk samples decreased after three days of storage at 20°C. Therefore, FTIR is a reliable method to be used for analysis of urea in raw milk, with the advantage of being a fast, efficient, versatile and low cost technique.